Hypo- and Hypermorphic FOXC1 Mutations in Dominant Glaucoma: Transactivation and Phenotypic Variability - Medina-Trillo, Cristina (PLoS One, 2015)
Dominant glaucoma, a heterogeneous, infrequent and irreversible optic neuropathy, is often associated with elevated intraocular pressure and early-onset. The role of FOXC1 in this type of glaucoma was investigated in twelve Spanish probands via nucleotide variation screening of its proximal promoter and unique exon. Functional evaluations of the identified variants included analyses of the transcriptional activity, protein stability, DNA binding ability and subcellular localization. Four different mutations that were identified in four probands (33.3%) were associated with remarkable phenotypic variability and were functionally classified as either hypermorphic (p.Y47X, p.Q106X and p.G447_G448insDG) or hypomorphic (p.I126S) alleles. To the best of our knowledge, three of the variants are novel (p.Y47X, p.I126S and p.G447_G448insDG) and, in addition, hypermorphic FOXC1 mutations are reported herein for the first time. The presence of an intact N-terminal activation domain in the truncated proteins p.Y47X and p.Q106X may underlie their associated transactivation hyperactivity by a gain-of-function mechanism involving dysregulated protein-protein interactions. Similarly, altered molecular interactions may also lead to increased p.G447_G448insDG activity. In contrast, the partial loss-of-function associated with p.I126S was due to impaired protein stability, DNA binding, protein phosphorylation and subcellular distribution. These results support that moderate and variable FOXC1 transactivation changes are associated with moderate goniodysgenesis, dominant glaucoma and remarkable phenotypic variability.